PERANCANGAN APLIKASI RENTAL MOBIL BERBASIS ANDROID DI RAMA RENT CAR - Ijan Candra; Nelly Astuti Hasibuan (SNASTIKOM, 2022)
Information technology plays an important role in improving the quality of institutions/companies. The development of information technology today is not only used in large organizations, but is also used by all sectors of society to support business or manage business. The increase in market business, especially car rental, is due to the high mobility of people in traveling by car. Rama Rent Car is a service that provides car rental/rental. At this time, business processes, transactions and storage still use conventional/manual systems, where the recording of all data processing processes is still using books. The purpose of this research is to create an android-based car rental/rental application that can help simplify all data processing processes contained in Rama Rent Car with a digital platform. This research uses MDLC method which starts from concept, design, collecting material, assembly, testing, to distribution. This android-based car rental application consists of several menus/features, namely, login menu, list menu, menu list,menu history transaction, and car menu. Tenants can borrow cars in the car menu, and can make transactions in themenu history transaction. Testing this car rental application usertesting blackbox to test whether this application is in accordance with what the user expects or not.. So, this android-based car rental application is suitable to be used to help the car loan process at Rama RentCar